Caracterización molecular y detección de genes blaCTX-M grupos 1 y 9 en Klebsiella pneumoniae resistentes a ceftazidima, en un hospital de San José de Cúcuta, Colombia (2019)
Background: The expression of CTX-M β-lactamases belonging to groups 1 and 9 in Klebsiella pneumoniae produces high levels of resistance to ceftazidime, and they have a wide distribution worldwide. Aim: To identify and characterize the blaCTX-M-Group1 and blaCTX-M-Group9 genes in K. pneumoniae isolates resistant to ceftazidime in a hospital in San José de Cúcuta, Colombia. Material and Methods: Primers were designed for the identification of K. pneumoniae and blaCTX-M genes by PCR. Subsequently, the genetic relationship of these isolates was analyzed by REP-PCR. Results: A 38% of the 24 isolates identified by PCR as K. pneumoniae showed blaCTX-M-3. blaCTX-M-15 y blaCTX-M-32 genes (Group CTX-M-1) and 42% blaCTX-M14. blaCTX-M-24 y blaCTX-M-27 genes (Group CTX-M-9). The phylogenetic analysis grouped the K. pneumoniae isolates into 4 clusters, showing correlation in clusters I, II and IV, when comparing the genetic profiles with the type of sample and group of genes. Discussion: We found a similar frequency of blaCTX-M-Group 1 and blaCTX-M-Group 9 genes in isolates of K. pneumoniae resistant to ceftazidime. The correlation between the REP-PCR with the CTX-M groups and the type of sample revealed the presence of three clonal pattern